In vitro anti-nephrotoxic potential of Ammi visnaga, Petroselinum crispum, Hordeum vulgare, and Cymbopogon schoenanthus seed or leaf extracts by suppressing the necrotic mediators, oxidative stress and inflammation - Marwa M. Abu-Serie; Noha H. Habashy; Adham M. Maher (BMC, 2019)
Abstract Background The kidney is an essential organ required by the body to perform several important functions. Nephrotoxicity is one of the most prevailing kidney complications that result from exposure to an extrinsic or intrinsic toxicant, which increase the need for the acquisition of proper remedies. Recently, natural remedies are gaining great attention owed to the fact that they have fewer side effects than most conventional drugs. Methods The current study recorded a new therapeutic role of the well-known medicinal plants for kidney stones [Ammi visnaga (AVE), Petroselinum crispum (PCE), Hordeum vulgare (HVE), and Cymbopogon schoenanthus (CSE)]. Hence, the aqueous extracts of these plants examined against CCl4-induced toxicity in mammalian kidney (Vero) cells. Results These extracts showed the presence of varying amounts of phenolic and triterpenoid compounds, as well as vitamin C. Owing to the antioxidant potential of these constituents, the extracts suppressed the CCl4-induced oxidative stress significantly (p < 0.05) by scavenging the reactive oxygen species and enhancing the cellular antioxidant indices. In addition, these extracts significantly (p < 0.05) reduced the CCl4-induced inflammation by inhibiting the gene expression of NF-кB, iNOS, and in turn the level of nitric oxide. Consequently, the morphological appearance of Vero cells, cellular necrosis, and the gene expression of kidney injury molecule-1 (a marker of renal injury) after these treatments were improved. The AVE improved CCl4-induced oxidative and inflammatory stress in Vero cells and showed a more potent effect than the commonly used alpha-Ketoanalogue drug (ketosteril) in most of the studied assays. Conclusion Thus, the studied plant extracts, especially AVE can be considered as promising extracts in the management of nephrotoxicity and other chronic diseases associated with oxidative stress and inflammation. Graphical abstract